2013
DOI: 10.3402/jom.v5i0.20939
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of bacterial counts from chronic periodontitis after root planing/scaling, surgery, and systemic and local antibiotics: 2-year results

Abstract: AimTo follow changes (over 2 years) in subgingival bacterial counts of five microbial complexes including health-related Actinomyces spp. in deeper pockets (≥5 mm) after periodontal treatments.MethodsEight different treatments were studied: (1) scaling+root planing (SRP); (2) periodontal surgery (SURG)+systemic amoxicillin (AMOX)+systemic metronidazole (MET); (3) SURG+locally delivered tetracycline (TET); (4) SURG; (5) AMOX+MET+TET; (6) AMOX+MET; (7) TET; and (8) SURG+AMOX+MET+TET. Antibiotics were given immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
(40 reference statements)
3
26
0
2
Order By: Relevance
“…4-8 The epithelial layer in the subgingival crevice is the initial interface between peridontopathic organisms and the host. 9, 10 The presence of bacteria in the subgingival environment can lead to the development of a biofilm, leading to an innate immune response associated with production of cytokines and anti-microbial peptides, reminiscent of responses at the mucosal interface in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…4-8 The epithelial layer in the subgingival crevice is the initial interface between peridontopathic organisms and the host. 9, 10 The presence of bacteria in the subgingival environment can lead to the development of a biofilm, leading to an innate immune response associated with production of cytokines and anti-microbial peptides, reminiscent of responses at the mucosal interface in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…It is stated that this is a short period to observe great changes in periodontal status over time, and that the major challenges for a breakdown or recurrence of the disease occur later in the maintenance phase. 2,8,37,41,42 Herein, microbiological findings in studies with more than 12 months showed in general stability along subsequent years. 23,24,29,34,37 The methodology for microbiological identification performed by most studies were qualitative or semi-quantitative analyses, when it is accepted that molecular identification and absolute quantification are the preferred techniques.…”
Section: Discussionmentioning
confidence: 85%
“…1,2,3,4,5 However, during the past 20 years the subgingival scaling and root planing (SBG) has been associated to that control and this association (SPG+SBG) been recognized as the choice therapy during periodontal maintenance period (PMP). 6,7,8 Nevertheless, studies comparing this combination to other protocols were not available until recently when a clinical study 9 and two systematic reviews 10,11 suggested that the SPG biofilm control alone might be the choice during PMP.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the optimal periodontal treatment as measured by changes in pocket depth and clinical attachment level, Mdala et al built a multilevel model with preconditions, such as smoking habits, and other predictors, such as bleeding and gingival redness (Mdala et al 2013). In a study that modeled the 30-day mortality after heart surgery, Sanagou et al examined multilevel models that included an array of prior conditions, such as preoperative dialysis, previous cardiac surgery, vascular disease, and others in a large effort that attempted to account for correlation between patients within hospitals (Sanagou et al 2012).…”
Section: Multilevel Models In Health and Medicinementioning
confidence: 99%
“…Specifically, after observing the importance of both preconditions and measures of entropy and change point analysis in Terner et al (2014b), we employ multilevel models to understand the interactions between these predictors. Previous works in health and medicine have used multilevel models for similar reasons: Mdala et al include preconditions in an effort to identify the periodontal treatment that best maintained clinical results over time (Mdala et al 2013); Bouwmeester reviews multilevel models as a prognostic prediction tool for patients undergoing anesthetized surgery (Bouwmeester 2012). We are interested in examining preconditions in concert with characteristics of the time series to develop a layered understanding of patient performance in these surgeries.…”
Section: Introductionmentioning
confidence: 99%